Metformin suppresses progression of muscle aging via activation of the AMP kinase-mediated pathways in Drosophila adults. - Suzuta, S.; Nishida, H.; Ozaki, M.; Kohno, N.; Le, T.D.; Inoue, Y.H. (European Review for Medical and Pharmacological Sciences, 2022)
Metformin, a medicine used for the treatment of type 2 diabetes, was previously reported to suppress age-dependent hyperproliferation of intestinal stem cells in Drosophila. Here, we aimed to investigate its anti-aging effects on other tissues, such as adult muscle and elucidate the mechanisms underlying the anti-ageing effect. To evaluate the anti-muscle ageing effect of Metformin, we visualized ubiquitinated protein aggregates accumulated in adult muscle as the flies age by immunostaining and measured the total pixel size of the aggregates. We altered gene expression in the muscle by induction of dsRNA against the relevant mRNAs or mRNAs encoding the constitutively active mutant proteins using the Gal4/UAS system. We determined the mRNA levels by quantitative Real Time-Polymerase Chain Reaction (QRT-PCR). Continuous metformin feeding significantly extended the lifespan of Drosophila adults. Furthermore, the feeding suppressed the aging-dependent accumulation of ubiquitinated aggregates in adult muscle. To delineate the mechanism through which metformin influences the muscle aging phenotype, we induced the constitutively active AMPK specifically in the muscles and found that the activation of the AMPK-mediated pathway was sufficient for the anti-aging effect of Metformin. Furthermore, the AMPK-mediated downregulation of Tor-mediated pathways, subsequent induction of an eIF-4E inhibitor were involved in the effect. These genetic data suggested that the metformin effect is related to the partial suppression of protein synthesis in ribosomes. Furthermore, metformin stimulated autophagy induction in adult muscles. Our results suggest that metformin can be regarded as an anti-aging compound in Drosophila muscle. The stimulation of autophagy was also involved in the anti-aging effect, which delayed the progression of muscle aging in Drosophila adults.